The differences in Indonesian ESL students’ motivation and perceptions of NEST and NNEST - Adara, Reza Anggriyashati (English Education Department, Faculty of Teacher Training and Education, Universitas PGRI Adi Buana Surabaya, 2020)
Different teachers might have different influence on students’ motivation as well as perceptions. The present study aims to analyse the differences in students’ motivation and perceptions toward of two different types of teachers; NEST (Native English Speaking Teachers) and NNEST (Non-Native English Speaking Teachers). The present study applied a mixed method approach by distributing a set of questionnaires to sixty junior high school students and interviewing four of them to answer its research questions. The results indicate students’ motivation to learn English with NEST because students think it will improve their speaking skills. In addition, NEST’ accents and cultural knowledge motivate students to learn English with them. On the other hand, the results suggest that students are motivated to learn English with NNEST because they are more understanding to students’ learning difficulties and NNEST can resort to students’ L1 when students need it. Thus, students seem to have their own perceptions of the disadvantages and advantages of NEST and NNEST. To minimise the disadvantages, co-teaching seems imperative to be conducted to improve students’ learning experience. In addition, pre-service teachers need to be aware of their own advantages and disadvantages either as NNEST or NEST. Educational institutions should also provide in-service teachers training to help their teachers reducing their disadvantages and maximising their advantages.